Експортна активність промисловості регіонів України: ключові тенденції - Іщук, С.О. (Економіка промисловості, 2016)
Здійснено групування регіонів України за значеннями інтегральних індексів експортної активності їх промисловості. Проаналізовано динаміку показників експорту промислових товарів упродовж 2011-2015 рр. Визначено ключові тенденції розвитку експортної діяльності промисловості в Україні та запропоновано комплекс заходів щодо ї активізації. Проведено группирование регионов Украины исходя из значений интегральных индексов экспортной активности их промышленности. Проанализирована динамика показателей экспорта промышленных товаров в течение 2011-2015 гг. Определены ключевые тенденции развития экспортной деятельности промышленности в Украине и предложен комплекс мер по её активизации. High share of industrial goods (over 60%) in the structure of export of goods and services confirms the determinative role of the industrial sector of economy in development of foreign trade in Ukraine. The aim of the article is to determine the level of export activity of the industry of regions of Ukraine and to develop the proposals for its further strengthening. By integrating the indices of industrial goods share in total export of goods and services, and the share of export in the volume of industrial products sold the indices of domestic industry export activity were calculated. The grouping of the regions of Ukraine by the integral indices revealed: 1) the average level of industry export activity is typical for the most regions (13 in 2015 against 8 in 2013); 2) high level was achieved in industrial eastern and border western regions; 3) low level is in southern and central regions.The analysis of the dynamics of industrial goods export indices was carried out. Positive and negative trends of the industry export activity in Ukraine during 2011-2015 were determined. A set of measures on diversification of industrial goods export structure, balance of industrial goods export structure in terms of trading partners of Ukraine, and gradual reorientation of investment flows to the development of high-tech manufacturing was proposed.